2020
DOI: 10.3390/ijerph17186568
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring in Chronic Pain Management Using Smartphone Apps: A Randomized Controlled Trial Comparing Usual Assessment against App-Based Monitoring with and without Clinical Alarms

Abstract: Background. The usefulness of mHealth in helping to target face-to-face interventions for chronic pain more effectively remains unclear. In the present study, we aim to test whether the Pain Monitor mobile phone application (app) is well accepted by clinicians, and can help improve existent medical treatments for patients with chronic musculoskeletal pain. Regarding this last goal, we compared three treatment conditions, namely usual treatment, usual treatment with an app without alarms and usual treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
3
17
0
7
Order By: Relevance
“…By attending to these data, the use of apps might be feasible to implement EMA in BTcP management. Additionally, as indicated in past research, the use of such apps for EMA could facilitate the implementation of clinical alarms embedded in the app, which could help to detect and respond to undesirable events (e.g., side effects of the medication or treatment non-adherence), which could ultimately improve quality of life in this population [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By attending to these data, the use of apps might be feasible to implement EMA in BTcP management. Additionally, as indicated in past research, the use of such apps for EMA could facilitate the implementation of clinical alarms embedded in the app, which could help to detect and respond to undesirable events (e.g., side effects of the medication or treatment non-adherence), which could ultimately improve quality of life in this population [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, we decided to use Pain Monitor, a validated app for the EMA of pain and related outcomes (e.g., fatigue, mood, and coping) [ 45 ]. The app, which was recently tested in a randomized controlled trial [ 38 ], involved pain experts in its development, was tested for interface problems (patient acceptability), and follows the current regulations in terms of data safety [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two of the studies included in this Special Issue focus on how ICT tools can be helpful in the screening and monitoring of different symptoms. Suso-Ribera et al [ 11 ] examined if the Monitor de Dolor app—which allows daily assessment of pain through ecological momentary assessments—would be an effective option for patient monitoring, in terms of improvement of chronic musculoskeletal pain management. The authors performed a randomized controlled trial in which they compared three conditions: the usual monitoring method (onsite retrospectively), usual monitoring plus app without alarms, and usual monitoring plus app with predefined alarms sent to clinicians to make treatment adjustments.…”
mentioning
confidence: 99%
“…Applications with clinician notification can improve outcomes for patients with chronic pain [ 28 ], but similar results have emerged in hospitalised patients. We had hypothesised that having access to a device to self-report pain would lead to improved analgesia by improving staff responsiveness, with a more marked effect when a specialist pain team was alerted [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bespoke treatment on the basis of user feedback represents an exciting opportunity to improve patient care. Suso-Ribera and colleagues showed that alerting clinicians to adverse symptoms entered remotely by patients with chronic pain led to a clinically significant improvement in a range of outcomes including depression, anxiety, pain interference, and severity when compared to usual treatment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%